Competence of ABEL Students in Constructing Sentences Using Sentence Patterns - Marissa Sison (Southeast Asian Journal of Science and Technology, 2017)
This study sought to determine the competence level of the 43 junior ABEL students in constructing sentences using different sentence patterns namely the S-IV; S-TV-DO; S-TV-IO-DO; S-TV-DO-OC; S-LV-PN; and S-LV-PA. The level of competence in constructing sentences was measured by an instrument which was researcher-made. Findings showed that the ABEL students were highly competent in using the sentence patterns S-IV, S-TV-DO, S-LV-PN, and S-LV-PA. whereas, their competence level in using S-TV-IO-DO was moderate while their competence level in suing S-TV-DO-OC was low. Thus, their over-all competence in constructing sentences was high. Chi-square correlation test results show that the competence level of the respondents had a moderate relation with their grades in Structure of the English Language and had a strong relation with their most preferred English reading materials. With these, students should exert more effort in studying the grammar or syntax of the English Language for them to improve their competence level.